Role of nano-fertilizers in improving productivity of peanut crop: A review - Waleed Al-Juheishy; Salim Ghazal (Mesopotamia Journal of Agriculture)
The quantity and quality of the macro- and micronutrients, such as phosphorus, potassium, calcium, Sulphur, iron, zinc, boron, and molybdenum, are crucial for agricultural production. The effectiveness of employing these fertilizers does not surpass 5% of the additive, despite the fact that these nutrients can be obtained from a variety of sources using chelating fertilizers and minerals, as well as addition techniques. By using alternative fertilizers to conventional fertilizers that are both environmentally responsible and highly effective, such as nano-fertilizers, it is better and important to diminish supplement misfortune during preparation and work to increment crop efficiency. As it manages materials and designs whose aspects range from 1-100 nm, nanotechnology is one of the contemporary technologies that has demonstrated good benefits in many domains, including agriculture, medicine, engineering, and energy. It was found that adding nano-fertilizers to the peanut crop (P, K, Ca, S, Fe, Zn, B, Mo) stimulated and accelerated growth as well as boosted production of this crop of pods and seeds.